Hyaluronic Acid Injections of the Knee: Predictors of Successful Treatment. Issue 7 (21st July 2017) - Bowman, Eric N.; Hallock, Justin; Azar, Frederick M.; Throckmorton, Thomas
Objectives: Knee viscosupplementation yields variable results for osteoarthritis. Establishing patient and treatment factors that predict a favorable response to intra-articular hyaluronic acid (HA) treatment will better guide patient and treatment selection. Methods: This prospective study evaluated patients presenting with Kellgren-Lawrence grade 1-3 painful, primary knee osteoarthritis. The primary outcome measures were the Western Ontario and McMaster Universities Arthritis Index/ Knee Injury and Osteoarthritis Outcome Score (WOMAC/KOOS) and a standardized visual analog scale (VAS). Surveys were completed at the first and subsequent injections, then at three months post-treatment. Response to treatment was defined according to the Osteoarthritis Research Society International 2004 criteria. Results: We enrolled 135 patients, 102 remained for final analysis. Fifty-seven percent of patients had a positive response to treatment. Factors related to a positive response included those with grade 1 or 2 osteoarthritis (RR=2.17; 95%CI, 1.40-3.37), and those who showed improvement after the first injection (RR=2.22; 95%CI, 1.49-3.31). Seventy-eight percent of people who responded to the first injection had a positive response at follow-up. In multi-variable analysis, those aged 60 or older responded more positively with grade 2 osteoarthritis than those less than 60 years (RR=1.98; 95%CI, 1.18-3.21). Gender, race, BMI, smoking status, HA brand, and initial VAS and KOOS scores were not significant predictors of success in either independent or multivariable analysis. Conclusion: Patients with mild to moderate osteoarthritis (grades 1 and 2), and those who responded positively to the first injection were two times more likely to respond positively to the injection series than those with grade 3 osteoarthritis, or those who did not respond initially. Patients aged 60 or older are twice as likely to respond than those less than 60 years for grade 2 osteoarthritis. Judicious patient selection and counseling may improve outcomes associated with intra-articular HA injections.Characteristics of patients according to successful treatment with hyaluronic acid. T-test probabilities are provided. Data are given as mean and standard or frequency and percent, as appropriate. Positive Response No Response N=58 (57%) N=44 (43%) P-value Age 61 (9.4) 59 (10.3) 0.436 Sex Male 16 (55) 13 (45) 0.830 Female 42 (58) 31 (42) BMI 33.2(6.2) 33.2 (8.4) 0.962 Smoking Status Non-smoker 51 (57) 39 (43) 0.914 Smoker 7 (58) 5 (42) Race White 48 (58) 35 (42) Black 10 (53) 9 (47) 0.683 OA Grade I 22 (85) 4 (15) II 21 (66) 11 (34) 0.001 III 15 (34) 29 (66) I st Injection Response Yes 40 (78) 11(22) 0.001 No 18 (35) 33(65) VAS Score Initial 6.1 (2.3) 5.2 (2.3) 0.066 2 nd Visit 4.4 (2.4) 4.4 (2.3) 0.924 Follow-up 2.4 (2.1) 5.1 (2.7) 0.001 Change in VAS 3.7 (2.0) 0.1 (2.0) 0.001